Gastroenterological disorders in inborn errors of immunity. Part 1. Epidemiology, classification, symptoms, diagnosis, and treatment - Napiórkowska-Baran, Katarzyna; Treichel, Paweł; Koperska, Kinga; Kudrej, Oliwia; Mućka, Natalia; Rajewska, Alicja; Wawrzeńczyk, Adam; Bartuzi, Zbigniew (Gastroenterology Review/Przegląd Gastroenterologiczny, 2025)
Inborn errors of immunity (IEI) are a heterogeneous group of genetic disorders affecting immune function, often presenting with diverse gastroenterological symptoms that pose diagnostic challenges. The latest classification developed by the International Union of Immunological Societies Experts Committee includes 582 IEI disease entities. Unfortunately, 70–80% of cases are still not recognized and do not enter the patient registers. Most cases are also diagnosed too late. This review explores the epidemiology, classification, symptoms, diagnostics, and treatment of gastrointestinal involvement in IEI.